Tari Inai: Identitas Budaya Masyarakat Desa Kuala Bangka, Kabupaten Labuhanbatu Utara - Qomariah, Siti; Sazali, Hasan; Batubara, Abdul Karim (Mahesa Research Center (PT. Mahesa Global Publishing), 2021)
This article discusses the Inai Dance in Kuala Bangka Village, North Labuhanbatu Regency. Inai Dance is a typical dance from the North Labuhanbatu Malay community which is usually performed at wedding processions. This study uses the historical method in four writing steps, namely; heuristics, verification or criticism, interpretation, and historiography, with a cultural approach. In its history, it is not known when and who brought the Inai Dance to Kuala Bangka Village. However, according to several sources, this tradition has long been practiced by the Malay community in this village. Inai Dance is a dance that comes from the acculturation of local culture with Arabic (Islamic) culture. This dance is usually performed by three dancers who will dance this dance in turn. Inai Dance is a dance that is performed during the procession of plain flour. This dance is performed in front of the bride and groom, apart from being an entertainment for the two brides, it also pays tribute to them as a king and queen for a day.